WORKLOAD ANALYSIS USING FULL TIME EQUIVALENT METHOD (Science and Technology (SciTech), 2022)
PT XYZ is an industrial company that produces various types of furniture. In running its business, PT XYZ has 2 warehouse locations to carry out production. There has been a production jam in warehouse 2 which caused the closure of warehouse 1. The results of observations have found an imbalance in production time between divisions. This research was conducted using the Full Time Equivalent (FTE) method, a workload analysis method that measures the length of time for completion of work. After that, an analysis of the workload and the optimal number of human resources for warehouse employees will be carried out. The results of this research, there has been a very high workload in the production division reaching 1.41 FTE. This figure exceeds the normal workload limit which has a range between 1~1.28 FTE. Data processing resulted in 2 different proposals to deal with these problems. First, recruiting 1 employee in the production division with the final result of reducing the burden to normal with a value of 1.06 FTE. Second, making 1 person in the material division work concurrently in the production division with the final result increasing the workload of the material division from 0.59 FTE to 0.79 FTE (underload) and decreasing the workload of the production division from 1.41 FTE to 1.21 FTE (normal).